2019
DOI: 10.1002/aic.16871
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoparticle morphology in the filtration efficiency and saturation of a silicon beads fluidized bed

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The corresponding activation energy is reported to be in between 29-38 kJ/mol and thus higher than what is required in the first step of VLS growth. The selectivity of the process could potentially be affected by hydrogenation/passivation of active surfaces at SiNWs and a-Si particles in the presence of H 2 gas, which could change the activation energy for the catalysed and non-catalysed reactions 33,34 and thus favour one of the products. This is unlikely though.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding activation energy is reported to be in between 29-38 kJ/mol and thus higher than what is required in the first step of VLS growth. The selectivity of the process could potentially be affected by hydrogenation/passivation of active surfaces at SiNWs and a-Si particles in the presence of H 2 gas, which could change the activation energy for the catalysed and non-catalysed reactions 33,34 and thus favour one of the products. This is unlikely though.…”
Section: Discussionmentioning
confidence: 99%
“…Eq. 8 and 9 have been succesfully used in studies of competing reactions during nanoparticle growth 34 , but not under variable hydrogen concentration. This can be included in the model by considering a simple silicon nanoparticles formation mechanism following the reaction:…”
Section: Kinetic Modelmentioning
confidence: 99%
“…With regard to industrial aerosols, it has been reported that many macroscopic properties of industrial relevance depend on the primary particle size and morphology defined in the initial stages of aerosol growth. (Neeleshwar et al 2005;Nguyen and Flagan 1991;Vazquez-Pufleau 2016;Vazquez-Pufleau and Yamane 2020;Vazquez-Pufleau 2019). Therefore, improving our understanding of the initial stages of aerosol growth can enhance our prediction capabilities for atmospheric phenomena and provide significant technological advances for industrial and medical (Diebolder et al 2018) applications.…”
Section: Introductionmentioning
confidence: 99%